Bridge architecture to interconnect hybrid wired/wireless PROFIBUS networks - Sousa, Paulo Baltarejo (2008)
The integration of wired and wireless technologies in modern manufacturing plants is now of paramount importance for the competitiveness of any industry. Being PROFIBUS the most widely used technology in use for industrial communications, several solutions have been proposed to provide PROFIBUS networks with wireless communications. One of them, the bridge-based hybrid wired/wireless PROFIBUS network approach, proposes an architecture in which the Intermediate Systems operate at Data Link Layer level, as bridges. In this paper, we propose an architecture for the implementation of such a bridge and the required protocols to handle communication between stations in different domains and the mobility of wireless stations.